Sedimentary and Source-to-Sink Evolution of Intracontinental Basins: Implications for tectonic and Climate Evolution in the Late Mesozoic (Southern Junggar Basin, NW China) - Guan, Xutong; Wu, Chaodong; Zhang, Xuecai; Jia, Weiwei; Zhang, Wei (Frontiers in Earth Science, 2022)
Sedimentary investigations, petrography, heavy mineral and conglomerate component analyses, and detrital zircon U-Pb geochronology were conducted to reconstruct the sedimentary and source-to-sink evolution of the Southern Junggar Basin, an intracontinental basin in the late Mesozoic. A paludal deltaic environment evolved into a fluvial environment, and abruptly prograded into alluvial fan and aeolian environments in the Late Jurassic, which was replaced by fan deltaic and lacustrine environments in the Early Cretaceous. Three source-to-sink systems were identified, according to different source-to-sink system features. In the northern piedmont of the Tianshan Orogenic Belt, the North Tianshan Orogenic Belt mainly provided sediments in the Late Jurassic. The North Tianshan and Central Tianshan Orogenic Belt both supplied sediments in the Early Cretaceous. In the northern piedmont of the Bogda Orogenic Belt, the Bogda Orogenic Belt was constantly the primary provenance, and the Tianshan Orogenic Belt also provided sediments. Sediment recycling occurred in the basin margin in the Late Jurassic and more metamorphic rocks were denudated in the Early Cretaceous. The source-to-sink system shrank in the Late Jurassic and expanded in the Early Cretaceous. This source-to-sink evolution and the conglomerates in the Kalazha Formation with seismite structures responded to the aridification in the Late Jurassic, the uplift of the Bogda and Tianshan Orogenic Belts in the Late Jurassic, and the exhumation of the Bogda and Tianshan Orogenic Belts in the Early Cretaceous.